Lightweight multi-principal-element hydrogen storage alloy with BCC structure and preparation method of lightweight multi-principal-element hydrogen storage alloy
Through secondary arc smelting and sectional heating and insulation heat treatment, a light multi-main hydrogen storage alloy with high-quality nitrogen storage density was prepared, which solved the high cost of existing hydrogen storage alloys. and the problem of low hydrogen storage density, efficient hydrogen storage and transportation have been achieved.
Patent Information
- Application Number
- CN202411589759.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-11
AI Technical Summary
The application of existing BCC structure hydrogen storage alloys is limited by cost and lower mass hydrogen storage density. Preparing lightweight hydrogen storage alloys to increase hydrogen storage density has become an urgent need.
The Ti-Cr-Mo-Al lightweight multi-main hydrogen storage alloy with BCC structure is prepared by adjusting the heating and insulation procedures of the heat treatment.
It has achieved high-quality hydrogen storage density, volume hydrogen storage density ≥140 g/L, mass hydrogen storage fraction ≥3.6 wt.%, and the alloy performance is stable, suitable for large-scale industrial applications.
Smart Images

Figure CN119410892A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen storage materials and relates to a lightweight multi-principal element hydrogen storage alloy with a BCC structure and a preparation method thereof. Background Art
[0002] Hydrogen energy has a wide range of sources, high fuel calorific value, zero pollution, and has the advantages of large-scale, long-term energy storage. It is an important carrier for the large-scale utilization of renewable energy and an important solution to environmental problems such as global warming. Important countries and regions around the world are increasing their investment in the hydrogen energy industry, and the hydrogen energy industry chain is being continuously constructed and improved. Hydrogen energy has initially achieved demonstration applications in the fields of hydrogen energy transportation and hydrogen energy storage.
[0003] The hydrogen energy industry is mainly divided into three parts: hydrogen production, hydrogen storage and transportation, and hydrogen application. Among them, hydrogen storage and transportation is an important link to connect upstream and downstream industries. The current mainstream hydrogen storage and transportation technology is high-pressure hydrogen storage, but it has the disadvantages of low hydrogen storage density and great safety hazards, and it is more prominent in the process of large-scale application and development of hydrogen energy. It is urgent to develop new safe and efficient hydrogen storage and transportation technologies. Solid-state hydrogen storage technology based on hydrogen storage alloys has the highest volume hydrogen storage density and safety performance among the current hydrogen storage technologies, and has the potential for large-scale promotion and application. The classic solid-state hydrogen storage alloy system is mainly divided into AB2, AB5 and V-based solid solution alloys. AB2-type alloys have high cycle life and low cost, but the hydrogen storage capacity is relatively low, about 1.8wt.%; AB5-type alloys have high cycle life and good power performance, but high cost and low hydrogen storage capacity, about 1.5 wt.%; V-based BCC-type hydrogen storage alloys have high hydrogen storage capacity, about 4.0 wt.%, good power performance, and high cycle life, but due to the high price of metal vanadium, the cost is extremely high. The octahedral and tetrahedral lattice gaps of the BCC structure can be used as hydrogen storage sites, and it is the crystal structure with the highest theoretical hydrogen storage capacity. Therefore, non-precious metal system alloys based on the BCC structure have great development potential. The Ti-Cr-Mo system with a BCC structure can not only produce a broad and flat hydrogen desorption platform area, but also produce a hydrogen capacity of 3.6 wt% close to that of V-containing alloys, which has great research value. In addition to cost, the key factor affecting the application of BCC structure hydrogen storage alloys is the low mass hydrogen storage density, and the preparation of lightweight hydrogen storage alloys is an effective measure to improve the mass hydrogen storage density. Element substitution is an effective means to obtain lightweight BCC structure hydrogen storage alloys. Commonly used lightweight hydrogen storage elements include Al, Mg, and Ti. Among them, the Mg-based alloy has a high hydrogen storage density, but the hydrogen absorption and desorption kinetics are poor. Al is the best lightweight alternative element choice. However, there is no technical disclosure of Ti-Cr-Mo-Al system BCC structure hydrogen storage alloys. Summary of the invention
[0004] In order to solve the above technical problems existing in the prior art, the present invention proposes a lightweight multi-principal element hydrogen storage alloy with a BCC structure and a preparation method thereof, which mainly adopts a method of secondary arc melting and segmented heating and insulation heat treatment, and prepares a BCC structure Ti-Cr-Mo-Al lightweight multi-principal element hydrogen storage alloy by adjusting the heating and insulation program of the heat treatment. The specific technical scheme is as follows: A method for preparing a lightweight multi-principal element hydrogen storage alloy with a BCC structure comprises the following steps: Step 1, proportioning the metal elements in the hydrogen storage alloy, the metal elements including Ti, Cr, Mo, and Al; Step 2: arc melting Ti, Cr, Mo, and Al metal elements in two stages. The first stage is arc melting Cr and Mo metal elements to obtain Cr-Mo intermetallic compounds. The second stage is arc melting the Cr-Mo intermetallic compounds with Ti and Al metal elements to obtain a cast alloy. Step 3, placing the cast alloy into a high-temperature resistant glass container which is evacuated and filled with high-purity argon gas, and sealing the container; Step 4: Perform a segmented heating and insulation heat treatment on the high-temperature resistant glass container after the sealing treatment in step 3, and immediately perform a gas quenching and cooling treatment after reaching the insulation time, so as to obtain a Ti-Cr-Mo-Al element hydrogen storage alloy.
[0005] Furthermore, in step 2, the smelting current of the first stage is 250-300A, the smelting time is 300s / time, and the number of smeltings is 1 time; the smelting current of the second stage is 100-200A, the smelting time is 200s / time, and the number of smeltings is 2-4 times.
[0006] Furthermore, the step three is specifically as follows: placing the cast alloy in a quartz tube, then evacuating the quartz tube and passing high-purity argon gas into the tube and then sealing the tube; then placing the quartz tube in another quartz tube, and similarly evacuating the other quartz tube and passing high-purity argon gas into the tube and then sealing the tube.
[0007] Furthermore, in step 4, the stepwise heating and heat preservation heat treatment is specifically as follows: when the temperature is raised from room temperature to 500°C, the heating rate is 10 o C / min, keep warm for 10 min, then continue to increase the temperature to 1000°C at a heating rate of 5°C / min, and then continue to increase the temperature to 1300°C at a heating rate of 1°C / min, and keep warm for 30 min.
[0008] Furthermore, in step 4, the gas pressure of the gas quenching and cooling treatment is 10 bar, the flow rate is 8 m / s, and the ventilation time is 10 min.
[0009] A lightweight multi-principal hydrogen storage alloy with a BCC structure, the chemical composition of the hydrogen storage alloy is Ti x Cr y Mo z Al r , where x , y , z , r is the atomic ratio, and 0.35≤ x ≤0.4、0.35≤ y ≤0.5、0.05≤ z ≤0.10、0.03≤ r ≤0.15.
[0010] Furthermore, the alloy density is ≤5.8kg / L, the volume hydrogen storage density is ≥140g / L, and the mass hydrogen storage fraction is ≥3.6wt.%.
[0011] Compared with the prior art, the present invention has the following beneficial effects: 1. The multi-principal element hydrogen storage alloy of the present invention is prepared by a double smelting method, which can melt Al and Mo, two metal elements with a melting point difference of nearly 2000°C, into an alloy, avoiding the uncontrollable loss of Al low-melting point alloy, and has the advantages of reliable operation and high repeatability.
[0012] 2. The multi-principal element hydrogen storage alloy of the present invention is prepared by a staged temperature-raising and heat-insulating heat treatment method, which is helpful to eliminate low-temperature impurities, so that the prepared BCC structure has higher purity and the alloy structure is more uniform.
[0013] 3. The multi-principal element hydrogen storage alloy of the present invention is prepared by gas quenching, which has a shorter cooling time, more uniform cooling, more convenient operation, lower cost and is suitable for large-scale industrial application compared to water quenching.
[0014] 4. The BCC structured Ti-Cr-Mo-Al lightweight multi-principal element hydrogen storage alloy prepared by the present invention has a relatively high mass hydrogen storage fraction, ≥3.6 wt.%, and a volume hydrogen storage density, ≥140 g / L.
[0015] 5. The BCC structure Ti-Cr-Mo-Al lightweight multi-principal element hydrogen storage alloy prepared by the present invention has stable performance, broad application prospects, and certain promotion and application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Ti prepared in Examples 1 and 2 of the present invention 0.38 Cr 0.47 Mo 0.12 Al 0.03 and Ti 0.37 Cr0.45 Mo 0.14 Al 0.04 Schematic diagram of the X-ray diffraction pattern of hydrogen storage alloy.
[0017] Figure 2 Ti prepared in Examples 1 and 2 of the present invention 0.38 Cr 0.47 Mo 0.12 Al 0.03 and Ti 0.37 Cr 0.45 Mo 0.14 Al 0.04 Schematic diagram of the hydrogen absorption and desorption coordinate curve of hydrogen storage alloy. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical scheme and technical effect of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0019] Example 1: Ti 0.38 Cr 0.47 Mo 0.12 Al 0.03 The preparation method of the multi-principal element hydrogen storage alloy is as follows.
[0020] According to the composition Ti 0.38 Cr 0.47 Mo 0.12 Al 0.03 The ingredients are prepared, and in the smelting process, Cr and Mo metal single substances are first smelted into Cr-Mo intermetallic compound, the smelting current is 250-300A, the smelting time is 300s / time, and the smelting number is 1 time; then the Cr-Mo intermetallic compound is eutectic with other metal single substances to obtain a cast alloy, the smelting current is 100-200A, the smelting time is 200s / time, and the smelting number is 3 times; The as-cast alloy is placed in a quartz tube with a diameter of 3 cm, and then the quartz tube is vacuumed and high-purity argon is introduced, and then the quartz tube is sealed, and then the quartz tube containing the alloy is placed in a quartz tube with a diameter of 4.5 cm again, and the quartz tube with a diameter of 4.5 cm is vacuumed and high-purity argon is introduced, and then the quartz tube is sealed for the second time; Then, the quartz tube after the second sealing is heat treated, and the temperature is raised from room temperature to 500℃ at a rate of 10 o C / min, keep warm for 10 minutes; then continue to increase the temperature to 1000℃ at a heating rate of 5℃ / min, and then continue to increase the temperature to 1300℃ at a heating rate of 1℃ / min, and keep warm for 30 minutes; after reaching the insulation time, immediately carry out gas quenching cooling treatment, the gas pressure of gas quenching cooling treatment is 10 bar, the flow rate is 8m / s, and the ventilation time is 10min.
[0021] Finally, the samples obtained above were cut into 3 mm cubes and the hydrogen storage properties of the alloys were measured using Sievert's method.
[0022] like Figure 1 As shown, the alloy prepared in Example 1 has a BCC single-phase structure.
[0023] like Figure 2 As shown, the maximum hydrogen storage capacity of the alloy prepared in Example 1 is 3.81wt.%.
[0024] Example 2: Ti 0.37 Cr 0.45 Mo 0.14 Al 0.04 The preparation method of the multi-principal element hydrogen storage alloy is as follows.
[0025] According to the composition Ti 0.37 Cr 0.45 Mo 0.14 Al 0.04 The ingredients are prepared, and in the smelting process, Cr and Mo metal single substances are first smelted into Cr-Mo intermetallic compound, the smelting current is 250-300A, the smelting time is 300s / time, and the smelting number is 1 time; then the Cr-Mo intermetallic compound is eutectic with other metal single substances to obtain a cast alloy, the smelting current is 100-200A, the smelting time is 200s / time, and the smelting number is 2 times; The as-cast alloy is placed in a quartz tube with a diameter of 3 cm, and then the quartz tube is vacuumed and high-purity argon is introduced, and then the quartz tube is sealed, and then the quartz tube containing the alloy is placed in a quartz tube with a diameter of 4.5 cm again, and the quartz tube with a diameter of 4.5 cm is vacuumed and high-purity argon is introduced, and then the quartz tube is sealed for the second time; Then, the quartz tube after the second sealing is heat treated, and the temperature is raised from room temperature to 500℃ at a rate of 10 o C / min, keep warm for 10 minutes; then continue to increase the temperature to 1000℃ at a heating rate of 5℃ / min, and then continue to increase the temperature to 1300℃ at a heating rate of 1℃ / min, and keep warm for 30 minutes; after reaching the insulation time, immediately carry out gas quenching and cooling treatment, the gas pressure of gas quenching and cooling treatment is 10 bar, the flow rate is 8m / s, and the ventilation time is 10min.
[0026] Finally, the samples obtained above were cut into 3 mm cubes and the hydrogen storage properties of the alloys were measured using Sievert's method.
[0027] like Figure 1 As shown, the alloy prepared in Example 2 has a BCC single-phase structure.
[0028] like Figure 2 As shown, the maximum hydrogen storage capacity of the alloy prepared in Example 2 is 3.75wt.%.
[0029] Example 3: Ti 0.35 Cr 0.40 Mo 0.15 Al 0.10 The preparation method of the multi-principal component alloy is as follows.
[0030] According to the composition Ti 0.35 Cr 0.40 Mo 0.15 Al 0.10 The ingredients are prepared, and in the smelting process, Cr and Mo metal single substances are first smelted into Cr-Mo intermetallic compound, the smelting current is 250-300A, the smelting time is 300s / time, and the smelting number is 1 time; then the Cr-Mo intermetallic compound is eutectic with other metal single substances to obtain a cast alloy, the smelting current is 100-200A, the smelting time is 200s / time, and the smelting number is 4 times; The as-cast alloy is placed in a quartz tube with a diameter of 3 cm, and then the quartz tube is vacuumed and high-purity argon is introduced, and then the quartz tube is sealed, and then the quartz tube containing the alloy is placed in a quartz tube with a diameter of 4.5 cm again, and the quartz tube with a diameter of 4.5 cm is vacuumed and high-purity argon is introduced, and then the quartz tube is sealed for the second time; Then, the quartz tube after the second sealing is heat treated, and the temperature is raised from room temperature to 500℃ at a rate of 10 o C / min, keep warm for 10 minutes; then continue to increase the temperature to 1000℃ at a heating rate of 5℃ / min, and then continue to increase the temperature to 1300℃ at a heating rate of 1℃ / min, and keep warm for 30 minutes; after reaching the insulation time, immediately carry out gas quenching cooling treatment, the gas pressure of gas quenching cooling treatment is 10 bar, the flow rate is 8 m / s, and the ventilation time is 10 minutes.
[0031] Finally, the samples obtained above were cut into 3 mm cubes, and the hydrogen storage performance of the alloy was measured by Sievert's method. The results showed that the alloy prepared in Example 3 was a BCC single-phase structure, and the maximum hydrogen storage capacity of the alloy was 3.64 wt.%.
[0032] Comparative Example 1: A multi-principal hydrogen storage alloy with the same chemical formula as in Example 1 was prepared. The chemical formula of the alloy was the same as that in Example 1, except that the preparation process was different. The preparation process of Comparative Example 1 was prepared according to the arc melting method in the prior art: Hu H, Tang R, Xiao H, He X, Zhou W, Zhang X, et al. Development of V-Free BCC Structured Alloys for Hydrogen Storage. ACS Applied Energy Materials. 2023, 6: 11108-11117. The specific process is as follows: According to the chemical composition Ti 0.38 Cr 0.47 Mo 0.12 Al 0.03 The ingredients are prepared, and Ti, Cr, Mo, and Al elements are directly eutectic during the smelting process. The smelting times are 4 times, and a cast alloy weighing 10 g is obtained; The cast alloy was heat treated at 1400°C for 10 min, then the heat treated alloy was crushed in air and ball milled into powder with a size of 100 μm. The hydrogen storage performance of the alloy was determined by Sievert's method.
[0033] Comparative Example 2: A multi-principal hydrogen storage alloy having the same chemical formula as in Example 1 was prepared, and two groups of samples A and B were prepared respectively. The chemical formula of the alloy was the same as in Example 1, and the preparation method was similar to that in Example 1, except that the heat treatment process during the preparation was different, as follows: Group A: The alloy samples were directly heated from room temperature to 1300°C at a rate of 5°C / min and kept at this temperature for 30 min.
[0034] Group B: The alloy samples were heated from room temperature to 1300°C at a heating rate of 1°C / min. ℃, keep warm for 30min.
[0035] The products prepared from Group A and Group B of Comparative Example 1 and Comparative Example 2 were subjected to a series of performance tests, and the results are as follows: The alloy prepared in Comparative Example 1 is not a BCC single-phase structure, and further contains 10% Laves segregation phase; the maximum mass hydrogen storage density of the alloy is 2.87 wt.%.
[0036] The alloy prepared in Group A of Comparative Example 2 is not a BCC single-phase structure, and further contains 15% Laves segregation phase; the maximum mass hydrogen storage density of the alloy is 2.83 wt.%.
[0037] The alloy prepared in Group B of Comparative Example 2 is not a BCC single-phase structure, but also contains 10% Laves phase structure and 17% Ti segregation phase; the maximum mass hydrogen storage density of the alloy is 3.01 wt.%.
[0038] Comparative Example 3: A multi-principal alloy having the same general chemical formula as in Example 1 is prepared. The chemical formula of the alloy is the same as in Example 1, and the preparation method is similar to that in Example 1. The only difference is the cooling method after heat treatment, which is as follows: The alloy sample was heated from room temperature to 500°C at a rate of 10°C / min, kept at this temperature for 10 min, then heated to 1000°C at a rate of 5°C / min, and then heated to 1300°C at a rate of 1°C / min, and kept at this temperature for 30 min.
[0039] After the insulation is completed, the alloy sample is naturally cooled in the furnace to obtain a multi-principal element hydrogen storage alloy.
[0040] The product prepared in Comparative Example 3 was subjected to a series of performance tests, and the results are as follows: The alloy prepared in Comparative Example 3 is not a BCC single-phase structure, and further contains 23% Laves segregation phase; the maximum mass hydrogen storage density of the alloy is 2.91 wt.%.
[0041] In summary, the preparation method of the present invention is simple, the process is easy to control, the prepared material has a stable structure, uniform alloy composition, uniform grain size, a mass hydrogen storage fraction of up to 3.81wt.%, and has excellent mass and volume hydrogen storage density, hydrogen absorption and desorption power, and cycle life.
[0042] The above is only a preferred implementation case of the present invention and does not limit the present invention in any form. Although the implementation process of the present invention is described in detail above, for those familiar with the art, they can still modify the technical solutions recorded in the above examples, or replace some of the technical features therein with equivalents. All modifications, equivalent replacements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a lightweight multi-principal element hydrogen storage alloy having a BCC structure, characterized in that: The following steps are involved: Step 1, proportioning the metal elements in the hydrogen storage alloy, the metal elements including Ti, Cr, Mo, and Al; Step 2: arc melting Ti, Cr, Mo, and Al metal elements in two stages. The first stage is arc melting Cr and Mo metal elements to obtain Cr-Mo intermetallic compounds. The second stage is arc melting the Cr-Mo intermetallic compounds with Ti and Al metal elements to obtain a cast alloy. Step 3, placing the cast alloy into a high-temperature resistant glass container which is evacuated and filled with high-purity argon gas, and sealing the container; Step 4: Perform a segmented heating and insulation heat treatment on the high-temperature resistant glass container after the sealing treatment in step 3, and immediately perform a gas quenching and cooling treatment after reaching the insulation time, so as to obtain a Ti-Cr-Mo-Al element hydrogen storage alloy.
2. The method for preparing a lightweight multi-principal element hydrogen storage alloy having a BCC structure according to claim 1, characterized in that: In step 2, the smelting current of the first stage is 250-300A, the smelting time is 300s / time, and the number of smeltings is 1 time; the smelting current of the second stage is 100-200A, the smelting time is 200s / time, and the number of smeltings is 2-4 times.
3. The method for preparing a lightweight multi-principal element hydrogen storage alloy having a BCC structure according to claim 1, characterized in that: The step three is specifically as follows: placing the cast alloy in a quartz tube, then evacuating the quartz tube and passing high-purity argon gas into the tube and then sealing the tube; then placing the quartz tube in another quartz tube, and similarly evacuating the other quartz tube and passing high-purity argon gas into the tube and then sealing the tube.
4. The method for preparing a lightweight multi-principal element hydrogen storage alloy having a BCC structure according to claim 1, characterized in that: In step 4, the stepwise heating and heat preservation heat treatment is specifically as follows: when the temperature is raised from room temperature to 500°C, the heating rate is 10 o C / min, keep warm for 10 min, then continue to increase the temperature to 1000°C at a heating rate of 5°C / min, and then continue to increase the temperature to 1300°C at a heating rate of 1°C / min, and keep warm for 30 min.
5. The method for preparing a lightweight multi-principal element hydrogen storage alloy having a BCC structure according to claim 1, characterized in that: In step 4, the gas pressure of the gas quenching and cooling treatment is 10 bar, the flow rate is 8 m / s, and the ventilation time is 10 min.
6. A lightweight multi-principal element hydrogen storage alloy prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The chemical composition of the hydrogen storage alloy is Ti x Cr y Mo z Al r , where x , y , z , r is the atomic ratio, and 0.35≤ x ≤0.4、0.35≤ y ≤0.5、0.05≤ z ≤0.10、0.03≤ r ≤0.
15.
7. The lightweight multi-principal element hydrogen storage alloy according to claim 6, characterized in that: Alloy density ≤5.8kg / L, volume hydrogen storage density ≥140g / L, mass hydrogen storage fraction ≥3.6wt.%.